The Impact of Public Transportation and Commuting on Urban Labour Markets: Evidence from the New Survey of London Life and Labour, 1929-32 - Andrew Seltzer; Jonathan Wadsworth (Institute of Labor Economics (IZA), 2021)
This paper examines the consequences of the commuter transport revolution on working class labour markets in 1930s London. The ability to commute alleviated urban crowding and increased workers' choice of potential employers. Using GIS-based data constructed from the New Survey of London Life and Labour, we examine the extent of commuting and estimate the earnings returns to commuting. We obtain a lower-bound estimate of two percent increase in earnings per kilometer travelled. We also show that commuting was an important contributor to improving quality of life in the early-twentieth century.
Keywords: N94; J39; N34; 330; public transportation; New Survey of London Life and Labour; GIS; earnings